What are the benefits and harms of testosterone replacement therapy (TRT) in men with low testosterone?. Issue 5 (May 2017) - Hamar, Matthew; Hostetter, Jeff
Abstract : EVIDENCE‐BASED ANSWER : In men with low testosterone and type 2 diabetes mellitus (DM2) or metabolic syndrome, TRT improves glycemic control, triglyceride levels, and body composition (SOR: C, meta‐analysis of disease‐oriented outcomes from RCTs). In men with low testosterone and frailty or low mobility, TRT does not result in clinically relevant improvements in muscle strength, body composition, or quality of life (SOR: B, 2 RCTs, 1 stopped early due to an increase in adverse cardiovascular events in TRT users). TRT is associated with an increased risk of death, myocardial infarction (MI) or stroke after adjustment for baseline comorbidities (SOR: B, one retrospective cohort).